PERAN PROGRAM PENDIDIKAN PROFESI GURU (PPG) DALAM MENINGKATKAN PROFESIONALISME GURU: SEBUAH TINJAUAN - Fitrah Qalbina Syahril; Meri Yulia; Hamdi Abdul Karim (Al-mujahidah, 2026)
This study aims to examine the role of the Teacher Professional Education Program (PPG) in improving teacher professionalism in educational institutions, particularly Islamic educational institutions. Teacher professionalism is a fundamental element in achieving high-quality and sustainable education. In Islamic educational institutions, teacher professionalism requires not only mastery of pedagogical and professional competencies, but also social and personality competencies integrated with religious values. PPG is a strategic government program to prepare competent and professionally certified teachers. Through this program, teachers are equipped with comprehensive competency development, from lesson planning and innovative learning implementation to developing professional attitudes in line with current demands and the character of educational institutions. This study employed a literature review method by examining various primary and secondary sources, such as reputable scientific journals, educational books, government regulations, and official documents related to the implementation of PPG in Indonesia. Data were analyzed qualitatively through a process of critical review, data reduction, and systematic interpretation. The results indicate that PPG plays a significant role in improving teachers' pedagogical, professional, social, and personality competencies. Furthermore, PPG also helps teachers design effective learning, implement innovative methods, and adapt learning approaches to the context of Islamic education. Thus, PPG is a strategic instrument for improving teacher quality and the overall quality of education